Basic Statistics - Parreno, Elizabeth B.; Jimenez, Ronel O. (Quezon City, 2006)
A comprehensive and easy-to-follow worktext designed to help Filipino students understand the fundamental concepts of statistics through practical examples and exercises.
Keywords: Statistics